Identifying sources of burnout among clinicians at a cancer center: A qualitative analysis. Issue 28 (1st October 2022) - Nguyen, Oliver; Alishahi, Amir; Moore, Colin Evan; Perkins, Randa; Bickel Young, Jennifer; Heimbeck, Dorte; Turner, Kea
Abstract : 429 Background: Clinician burnout leads to increased job turnover and workforce shortages, and reduced patient satisfaction and quality of care. Despite its importance, there has been limited study of burnout among the cancer care workforce including sources of burnout. This information can be used to inform intervention design for use in the cancer care setting specifically. To address this gap, we analyzed open-ended responses to a well-being survey administered to clinicians (physicians and advanced practice providers) at a Cancer Center. Methods: In February 2022, we electronically administered the American Medical Association's clinician well-being survey to all practicing clinicians at a National Cancer Institute-designated Comprehensive Cancer Center in Florida. Of 700 clinicians, 405 (58%) responded. Of the respondents, 259 (64.0%) answered the free-text question "Tell us more about your stressors and what we can do to minimize them." We used in-vivo coding to develop qualitative themes across responses. If a given response incorporated multiple themes, we coded the response under all pertinent themes. Results: A majority (76/259) of respondents commented on staffing issues, such as their clinics being understaffed or the quality of current staff. Another frequent theme (64/259) was the electronic health records (EHR) system, such as lack of integration between modules, inbox fatigue, alert fatigue, and inefficient documentation review processes. Respondents also reported scheduling issues as a pain point (56/259), such as having schedules that do not reflect actual clinical practice, being overbooked, and scheduling errors. Documentation burden was also highlighted as an issue across respondents (34/259). Documentation was considered tedious and some respondents reported a mismatch between available documentation tools in the EHR and actual documentation needs. Less common themes reported across respondents included design issues of facility space (e.g., no dedicated workspace to complete work without interruptions) and insufficient time to complete administrative, research, and documentation requirements. Conclusions: Our findings suggest that interventions that optimize staffing models, EHR processes (e.g., documentation), and scheduling practices may reduce burnout for a considerable number of cancer care clinicians.